Land, rights and the politics of investments in Africa : ruling elites, investors and populations in natural resource investments - Buur, Lars; Macuane, José J.; Maganga, Faustin P.; Pedersen, Rasmus H. (Edward Elgar Publishing, 2023)
"In response to the recent surge in extractive natural resource investments in Africa, this insightful book explores how relations between investors, ruling elites, and local populations develop when large-scale investments in gas, minerals, and agriculture expand. Advancing a multi-level approach that encompasses rigorous theoretical analysis, fieldwork, and literature review, expert contributors examine the implementation of natural resource investments and the extent to which they respect procedural rights of local populations. Chapters draw together understudied bodies of literature on land-grabbing debates, the resource curse controversy and corporate social responsibility (CSR), demonstrating how the chances of large-scale investments in natural resources are at their greatest when characterised by 'reciprocal exchange deals' between investors and local populations, 'compatible interests' between ruling elites and investors, and 'mutual recognition' between local populations and ruling elites. Through a careful examination of case studies in Mozambique, Tanzania, and Uganda, the book ultimately highlights the complexity of the political economy of natural resource investments. Providing valuable theoretical and empirical insights, this book will be an invigorating read for scholars and students of political economy, political geography, sustainability, CSR, and business studies. Its valuable insights on how natural resource investments might accelerate economic growth and consolidate links between local and global economies will also be of interest to development practitioners and investors"--